2023
DOI: 10.1002/anie.202309913
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow‐loss Optical Waveguides through Balancing Deep‐Blue TADF and Orange Room Temperature Phosphorescence in Hybrid Antimony Halide Microstructures

Abstract: Harnessing the potential of thermally activated delayed fluorescence (TADF) and room temperature phosphorescence (RTP) is crucial for developing light‐emitting diodes (LEDs), lasers, sensors, and many others. However, effective strategies in this domain are still relatively scarce. This study presents a new approach to achieving highly efficient deep‐blue TADF (with a PLQY of 25%) and low‐energy orange RTP (with a PLQY of 90%) through the fabrication of lead‐free hybrid halides. This new class of monomeric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 77 publications
0
26
0
Order By: Relevance
“…are preferred to avoid strong SOC that enhances phosphorescence emission from T 1 to S 0 . [67][68][69] Yan's group has conducted representative research on LDMHs with TADF properties based on 4-hydroxypyridine, benzotriazole and tetraphenylphosphonium. 68,[70][71][72] Taking 4HP (4HP = 4-hydroxypyridine) as an example, Yan et al demonstrated a 2D blue light-emitting metal halide CdCl 2 -4HP with efficient TADF emission (Fig.…”
Section: Thermally Activated Delayed Fluorescencementioning
confidence: 99%
“…are preferred to avoid strong SOC that enhances phosphorescence emission from T 1 to S 0 . [67][68][69] Yan's group has conducted representative research on LDMHs with TADF properties based on 4-hydroxypyridine, benzotriazole and tetraphenylphosphonium. 68,[70][71][72] Taking 4HP (4HP = 4-hydroxypyridine) as an example, Yan et al demonstrated a 2D blue light-emitting metal halide CdCl 2 -4HP with efficient TADF emission (Fig.…”
Section: Thermally Activated Delayed Fluorescencementioning
confidence: 99%
“…Due to the increasing demand for clean-energy lighting materials, copper halide-based organic–inorganic hybrid structures are a growing family of compounds that are gaining attention for their intriguing luminescent properties. 1–11 This diverse family of compounds warrants more research to better understand their structure–property correlations in order to design new structures with better performance. 12–15 A variety of inorganic building motifs have already been reported for copper halide-based structures, with the most common being a Cu 2 X 2 rhomboid dimer, a Cu 4 X 4 cubane tetramer, and a (CuX) ∞ staircase chain (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 For example, Xiao et al constructed a new supramolecular hydrogel using 1,4-diaminobenzene (DB) and hexamethyl cucurbit [5]uril (HmeQ [5]) by the host−guest interaction, and then embedded 6-bromo-2-naphthol (BrNp) exhibited fluorescent−phosphorescence double emissions due to the rigid microstructure. 11 Multicolor luminescence, 12 especially multicolor RTP materials, 13 is a hot topic in the field of chemical materials. However, there are still some limitations in the regulation of the RTP emission.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, supramolecular systems with room-temperature phosphorescence (RTP) have been considered as more advantageous luminescent materials due to the distinctive properties, such as large Stokes shift and long triplet lifetime. The macrocyclic confinement effect and the reversibility of supramolecular systems have attracted increasing research efforts to effectively enhance RTP through noncovalent interactions. The encapsulation of macrocyclic hosts could restrict molecular motion of phosphorescent guests and even promote intersystem crossing (ISC) to enhance RTP emission. , In addition, the abundant hydrogen bonding interactions and ordered spatial structure of supramolecular assemblies supply a rigid microenvironment, which is able to stabilize the triplet state and inhibit nonradiative transitions to promote RTP. , For example, Xiao et al constructed a new supramolecular hydrogel using 1,4-diaminobenzene (DB) and hexamethyl cucurbit[5]­uril (HmeQ[5]) by the host–guest interaction, and then embedded 6-bromo-2-naphthol (BrNp) exhibited fluorescent–phosphorescence double emissions due to the rigid microstructure . Multicolor luminescence, especially multicolor RTP materials, is a hot topic in the field of chemical materials. However, there are still some limitations in the regulation of the RTP emission.…”
Section: Introductionmentioning
confidence: 99%